Fabrication of Function‐Graded Proton Exchange Membranes for Direct Methanol Fuel Cells Using Electron Beam‐Grafting. Issue 2 (17th March 2014) - Tsuchida, R.; Hiraiwa, S.; Tsukamoto, A.; Washio, M.; Oshima, A.
Abstract Function‐graded proton exchange membranes (G‐PEMs) based on poly(tetrafluoroethylene‐co‐hexafluoropropylene) were fabricated for direct methanol fuel cells (DMFCs) via electron beam‐grafting using the heterogeneous energy deposition technique. The G‐PEMs had a water uptake gradient in the proton transfer direction, originating from the sulfonic acid group gradient. The distribution of sulfonic acid groups in the various G‐PEMs was evaluated using X‐ray photoelectron spectroscopy. Four types of PEMs (flat‐type, strong‐gradient, meso‐gradient, and weak‐gradient types) were fabricated. By varying the direction of the G‐PEMs, the methanol permeation test and DMFC operation were performed with two orientations of the sulfonic acid group gradient, decreasing from the methanol injection (anode) side (decrease‐type) or the other (cathode) side (increase‐type). The methanol permeability of the strong‐gradient, meso‐gradient, and weak‐gradient G‐PEMs was lower than that of Nafion®117 and the flat‐type PEM. The "increase‐type" orientation of the strong‐gradient G‐PEM resulted in the lowest methanol permeability. The DMFC performance of the G‐PEMs was influenced by the thickness direction, such as "decrease‐type" and "increase‐type." The performance of the "decrease‐type" assembly was higher than that of the "increase‐type." The "decrease‐type" assembly with P‐200 k (weak‐gradient G‐PEM) exhibited the highest performance of the fabricated PEMs, comparable to that of Nafion®117.